QUANTITATIVE-ANALYSIS OF NORTH-SEA SUBSIDENCE - Thorne, J; Watts, A (1989)
Stratigraphic and geophysical maps of the northern and southern North Sea basin are used to study mechanisms of intracratonic basin formation. In northern areas of the North Sea, observed basement-fault extension, crustal thinning, present-day flexural rigidity, and tectonic subsidence are predicted reasonably well by a simple stretching model of basin formation with rifting phases during the Triassic and mid-Jurassic/Early Cretaceous. In southern areas of the North Sea, however, a similar analysis suggests that other non-extensional rift-related processes dominated basin evolution. The effects of anomalously active aesthenospheric convection, coupled with basalt-eclogite and deep-crustal dewatering reactions, are considered as possible additional mechanisms. The troughlike form of Quaternary tectonic subsidence suggests a new phase of rifting may be starting in the North Sea.